Development of an equipment cleaning validation guideline for the Philippine pharmaceutical manufacturers - Barangan, Ma. Rosario B.
The requirement that equipment should be clean prior to use is nothing new. The 1963 United States Food and Drug Administration (US FDA) Good Manufacturing Practices (GMP) Guidelines stated "Equipment ...shall be maintained in clean and orderly manner..." In July 1993, the US FDA issued the "Guide to Inspections of Validation of Cleaning Processes." Other similar guidelines followed, such as, the Pharmaceutical Inspection Convention/Pharmaceutical Inspection Cooperation Scheme (PIC/S), 2001 recommendation, the World Health Organization (WHO) 1997 guide, the European Union (EU) 2001 guide and the Health Canada 2000 guidelines. The Philippine government, recognizing the importance of improving the quality of products in the country to international standards similar to that in America and Europe, issued the 2000 Philippine Current Good Manufacturing Practices (cGMP) to serve as a guideline for companies and Bureau of Food and Drugs (BFAD) inspectors. Cleaning Validation is not specifically stated in the 2000 Philippine cGMP. This would cause a lot of conflict and confusion for both the pharmaceutical manufacturers and BFAD. Multi-product facilities are of great concern for manufacturers and regulatory agencies with the risk of cross contamination of different products running on the same lines. Cost must also be considered because of the substantial investment that validation entails. A Cleaning Validation Guideline aligned with the current international requirements was developed, to assist the Philippine regulatory agency and pharmaceutical dosage form manufacturers facilitate compliance with the cleaning validation requirement of cGMP. Guidelines from the different regulatory bodies such as, US FDA, EU, Health Canada, WHO and PIC/S were reviewed and compared. Current literatures on cleaning validation were also reviewed to obtain updated information. Industry practices were discussed with experts from different pharmaceutical companies during international symposia on validation and compliance. Suppliers of detergents were also consulted for some technical assistance regarding establishing acceptable limits of detergents.
The guideline specifically addressed the following: 1) required documentation, 2) personal training, 3) equipment/systems analysis, 4) computation of residue acceptance levels, 5) determination of worst case product, 6) detection methods validation, 7) sampling methods validation and recovery study, 8) conduct of cleaning validation studies. The developed cleaning validation guideline was adopted in the cleaning validation of the multi-product solid dosage form facility of E.L. Laboratories, Inc. (ELLI). The cleaning process of ELLI's tablet processing line was successfully validated. The guideline would provide the Philippine pharmaceutical dosage form manufacturers and regulatory agency, BFAD, a common reference and understanding in performing and evaluating equipment cleaning validation. The guideline will facilitate compliance with the Department of Health AdministrativeOrder No. 43-A Series of 1999, Amendment of Administrative Order No. 220s. 1974, Current Good Manufacturing Practice, with minimal costs. The study on the validation of the cleaning process of ELLI's tablet processing line showed that with a clear guideline, a company is capable of performing cleaning validation
Available to the general public.
Thesis (Master of Science in Industrial Pharmacy)--University of the Philippines Manila, March 2005.
Keywords: Drugs -- Sterilization; Clean rooms; Pharmaceutical industry -- Quality control